Exoteric and Esoteric Values of the Ḥajj in Syair Haji by ‘Abd al-Ḥamīd: A Ricoeurian Hermeneutic Study - Rosalinda, Rosalinda; Ilham, Andri; Nurdin, Nurdin (Jurnal Adabiyah, 2026)
This study aims to examine the exoteric dimension and esoteric values of the pilgrimage (ḥajj) contained in Syair Haji by Sheikh ‘Abd al-Ḥamīd through Paul Ricoeur’s hermeneutical approach. As a work of religious literature, Syair Haji embodies spiritual messages and mystical experiences that reflect the inner journey of a ḥajj in pursuing the divine dimension. Ricoeur’s hermeneutical method is employed to interpret the text deeply through the processes of literal, reflective, and interpretative understanding, thereby uncovering the symbolic and existential layers of meaning within the poem. The results of the study show that Syair Haji by Shaykh ‘Abd al-Ḥamīd is not merely a reflection of the poet’s spiritual experience, as is commonly found in Syair Haji, but also contains a concept of integration between the exoteric dimension and the esoteric values of the pilgrimage. The ḥajj prescribed in Islam is an act of worship grounded in the sharī‘ah to ensure conformity with religious law, while the esoteric dimension of ḥajj aims to attain its spiritual essence. The exoteric aspect of ḥajj represents complete obedience to the divine law, whereas the esoteric aspect relates to ma‘rifatullāh the intimate knowledge of God through a purified heart. This study is expected to contribute to the development of Sufi literary studies and the application of hermeneutics in the interpretation of religious literary works. Furthermore, it aims to enrich contemporary Arabic literary scholarship, particularly in the fields of religious and mystical literature. الملخص تهدف هذه الدراسة إلى تحليل البعد الظاهري والقيم الباطنية لفريضة الحج في قصيدة الحج للشيخ عبد الحميد من خلال منهج التأويل عند بول ريكور. فهذه القصيدة، باعتبارها عملا أدبيا دينيا، تتضمن رسائل روحية وتجارب صوفية تعبّر عن الرحلة الباطنية للحاج في سعيه إلى البعد الإلهي. وقد تم توظيف منهج التأويل الريكوري لتحليل النص تحليلا عميقًا عبر مراحل الفهم الحرفي والتأملـي والتفسيري، بغية الكشف عن الطبقات الرمزية والوجودية الكامنة في القصيدة. تظهر نتائج الدراسة أنّ شعر الحجّ للشيخ عبد الحميد لا يقتصر على كونه انعكاسا للتجربة الروحية للشاعر، كما هو الحال في قصائد الحج عموما، بل يتضمن مفهوما تكامليا يجمع بين البعد الظاهري للحج وقيمه الباطنية والروحية. فالحج الذي شُرِع في الإسلام هو عبادة تقوم على الشريعة لضمان التزامها بأحكام الدين، في حين يهدف البعد الباطني للحج إلى بلوغ جوهره الروحي. إن البعد الظاهري للحج يمثل الطاعة الكاملة لأوامر الله، بينما يرتبط البعد الباطني بـمعرفة الله (المعرفة الإلهية) التي تتحقق بقلبٍ طاهرٍ متطهّر. ومن المتوقع أن تُسهم هذه الدراسة في تطوير الدراسات الأدبية الصوفية وتطبيق منهج التأويل في فهم النصوص الأدبية الدينية، كما تهدف إلى إثراء البحث الأدبي العربي المعاصر، ولا سيما في مجالي الأدب الديني والأدب الصوفي. Abstrak Penelitian ini bertujuan untuk mengkaji eksoteris dan nilai esoteris ibadah haji yang terkandung dalam Syair Haji karya Syeikh ‘Abd al-Ḥamīd dengan pendekatan hermeneutika Paul Ricoeur. Syair Haji sebagai karya sastra keagamaan mengandung pesan spiritual dan pengalaman mistik yang merefleksikan perjalanan batin seorang haji dalam menapaki dimensi ketuhanan. Metode hermeneutika Ricoeur digunakan untuk menafsirkan makna teks secara mendalam melalui proses pemahaman literal, reflektif, dan interpretatif, sehingga dapat mengungkap lapisan makna simbolik dan eksistensial dalam syair tersebut. Hasil kajian menunjukkan bahwa Syair Haji karya Syeikh ‘Abd al-Ḥamīd tidak hanya refleksi pengalaman spiritual penyair seperti syair haji pada umumnya, tetapi mengandung konsep integrasi antara keberadaan eksoteris dan nilai esetoris haji. Haji yang diperintahkan dalam Islam adalah haji yang berangkat dari syariah sebagai landasan sehingga tidak menyalahi aturan, sementara itu keberadaan esetoris haji untuk mencapai esensi haji.  Konsep eksoteris haji adalah ketaatan total kepada hukum Allah, sementara esoteris haji adalah ma’rifatullah yaitu mengenal Allah dengan hati yang telah disucikan.  Penelitian ini diharapkan dapat memberikan kontribusi pada pengembangan studi sastra tasawuf serta pemahaman hermeneutika dalam konteks karya sastra keagamaan. Penelitian ini diharapkan memperkaya kajian sastra Arab kontemporer khususnya dalam bidang sastra religius dan tasawuf.